Engineering Luminescence Lifetimes of Cu(I) Complexes for Optical Multiplexing. Issue 23 (11th October 2018) - Ma, Yun; Dong, Yafang; She, Pengfei; Liu, Shujuan; Xie, Mingjuan; Yu, Yaxin; Li, Yonghua; Zhao, Qiang; Huang, Wei
Abstract: Luminescent materials with tunable emission lifetimes have gained broad research interest, because they are ideal candidates for optical multiplexing applications, such as biolabeling, security printing, and data storage. To date, a few studies have reported that the efficient regulation of emission decay times can be achieved for lanthanide nanomaterials. However, it remains challenging to engineer the luminescence lifetimes of small molecules due to the lack of effective methods. Herein, a new strategy is put forward to control the emission lifetimes of ionic Cu(I) complexes by changing the electrostatic interactions between cationic complexes and counter anions. The Cu(I) complexes prepared with different counterions (ClO4 −, PF6 −, NO3 −, and BF4 − ) exhibit distinct luminescence lifetimes from 12.9 to 22.3 µs in the solid state. Importantly, by simply doping different contents of CuBF4 into polymethyl methacrylate, the emission lifetimes could be varied in a linear manner in the range from 11.4 ± 0.3 to 20.7 ± 0.2 µs. Based on the tunable emission lifetimes, optical multiplexing is achieved by using time‐resolved luminescence imaging technique. Abstract : A series of Cu(I) complexes containing different counterions is prepared to demonstrate that their luminescence lifetimes can be controlled by electrostatic interaction. By doping different contents of Cu(I) complexes into polymethyl methacrylate (PMMA) matrices, the variations in emission lifetime show a good linear correlation. Based on this tunable emission lifetime, optical multiplexing is achieved by using time‐resolved luminescence imaging technique.